1985
DOI: 10.1016/0165-0378(85)90051-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cellular cytotoxic activities of colostral lymphocytes and maternal peripheral blood lymphocytes

Abstract: Colostral lymphocytes (CL) from mothers 2 to 4 days post-partum and autologous maternal peripheral blood lymphocytes (PBL) were investigated for (1) natural killer (NK) and antibody-dependent cellular cytotoxic (ADCC) activities, (2) target binding ability, (3) interferon (IFN)- and interleukin 2 (IL2)-induced augmentation of NK activity, (4) lectin-dependent cellular cytotoxicity (LDCC), and (5) the ability of culture-derived soluble suppressor factor(s) to inhibit the NK activity of normal allogeneic lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…These reports are consistent with reports that neutrophils recovered from human mammary secretions showed a reduction in functionality, e.g. motility, phagocytosis, respiratory burst, and PMN (polymorphonuclear) cell-mediated cytotoxicity, compared with serum-derived cells (Kohl and Loo, 1980; Nair et al , 1985; Schollenberger et al , 1986; Özkaragöz et al , 1988).…”
Section: Immunological Functions Of Mammary Secretionssupporting
confidence: 90%
“…These reports are consistent with reports that neutrophils recovered from human mammary secretions showed a reduction in functionality, e.g. motility, phagocytosis, respiratory burst, and PMN (polymorphonuclear) cell-mediated cytotoxicity, compared with serum-derived cells (Kohl and Loo, 1980; Nair et al , 1985; Schollenberger et al , 1986; Özkaragöz et al , 1988).…”
Section: Immunological Functions Of Mammary Secretionssupporting
confidence: 90%
“…Cumulatively, these studies suggested that phagocytic cells in swine mammary secretion are capable of phagocytosis, but may lack some intracellular functions. This reports are consistent with reports that neutrophils recovered from human mammary secretions showed a reduction in functionality, e.g., motility, phagocytosis, respiratory burst, and polymorphonuclear (PMN)-mediated cytotoxicity, compared to serum-derived cells Nair et al, 1985;Ozkaragoz et al, 1988;Schollenberger et al, 1986).…”
Section: Phagocytic Cellssupporting
confidence: 90%
“…Separation of lymphocytes from other milk cells is a difficult task, and the use of unseparated cells risks the release from accessory cells of preformed IgA, and possibly suppressive substances (22), into the culture system. Early work from our lab suggests that BM B-cells may be regulated in a unique fashion by the products they elaborate (23).…”
Section: Resultsmentioning
confidence: 99%